The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1071/rd08036
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylacetamide can be used as an alternative to glycerol for the successful cryopreservation of koala (Phascolarctos cinereus) spermatozoa

Abstract: Swelling of koala sperm chromatin following cryopreservation has largely been attributed to the absence of intermolecular disulfide cross-linkages in the marsupial sperm nucleus. Fish spermatozoa also lack disulfide bonds within their chromatin, but have been successfully cryopreserved. The present study examined the hypothesis that the cryoprotectants used for fish sperm cryopreservation would confer a similar degree of protection on koala spermatozoa. Three concentrations each of five cryoprotectants (dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…These results are consistent with other studies which show that the osmotic stress associated with thawing is likely to be most detrimental to the spermatozoa during the cryopreservation procedure (Holt et al 1992). The post-thaw membrane integrity reported in this study was higher than that reported in other studies on koala sperm examined immediately after cryopreservation (Johnston et al 2006, Zee et al 2008, 2009a and reflects the fact that spermatozoa in the current study were examined 30 min after thawing; however, it should be noted that these studies have also reported a rapid decline in PMI of these same spermatozoa after 120 min of incubation at 35 8C. These observations draw attention to the importance of induced damage associated with ex vivo handling (so-called 'iatrogenic damage') and the variable survival time of spermatozoa when incubated within in vitro environments that attempt to mimic the physiology of the female reproductive tract.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are consistent with other studies which show that the osmotic stress associated with thawing is likely to be most detrimental to the spermatozoa during the cryopreservation procedure (Holt et al 1992). The post-thaw membrane integrity reported in this study was higher than that reported in other studies on koala sperm examined immediately after cryopreservation (Johnston et al 2006, Zee et al 2008, 2009a and reflects the fact that spermatozoa in the current study were examined 30 min after thawing; however, it should be noted that these studies have also reported a rapid decline in PMI of these same spermatozoa after 120 min of incubation at 35 8C. These observations draw attention to the importance of induced damage associated with ex vivo handling (so-called 'iatrogenic damage') and the variable survival time of spermatozoa when incubated within in vitro environments that attempt to mimic the physiology of the female reproductive tract.…”
Section: Discussionsupporting
confidence: 92%
“…Koala semen cryopreservation has been described previously (Johnston et al 2006, Zee et al 2008. Briefly, each ejaculate was initially diluted (1:1) with warm (35 8C -normal koala body temperature) TCG buffer in a pre-warmed 1.5 ml microcentrifuge tube (Eppendorf AG, Hamburg, Germany) and allowed to cool to room temperature (25 8C) over a period of 10 min.…”
Section: Sperm Preparationmentioning
confidence: 99%
See 3 more Smart Citations